Increase in DNA Damage by MYCN Knockdown Through Regulating Nucleosome Organization and Chromatin State in Neuroblastoma - Hu, Xinjie; Zheng, Weisheng; Zhu, Qianshu; Gu, Liang; Du, Yanhua; Han, Zhe; Zhang, Xiaobai; Carter, Daniel R.; Cheung, Belamy B.; Qiu, Andong; Jiang, Cizhong (Frontiers in Genetics, 2019)
As a transcription factor, MYCN regulates myriad target genes including histone chaperone FACT. Moreover, FACT and MYCN expression form a forward feedback loop in neuroblatoma. It is unclear whether MYCN involves in chromatin remodeling in neuroblastoma through regulating its target genes. We showed here that MYCN knockdown resulted in loss of the nucleosome free regions through nucleosome assembly in the promoters of genes functionally enriched for DNA repair. The active mark H3K9ac was removed or replaced by the repressive mark H3K27me3 in the promoters of double-strand break repair-related genes upon MYCN knockdown. Such chromatin state alterations occurred only in MYCN-bound promoters. Consistently, MYCN knockdown resulted in a marked increase in DNA damage in the treatment with hydroxyurea. In contrast, nucleosome reorganization and histone modification changes in the enhancers largely included target genes with tumorigenesis-related functions such as cell proliferation, cell migration, and cell-cell adhesion. The chromatin state significantly changed in both MYCN-bound and MYCN-unbound enhancers upon MYCN knockdown. Furthermore, MYCN knockdown independently regulated chromatin remodeling in the promoters and the enhancers. These findings reveal the novel epigenetic regulatory role of MYCN in chromatin remodeling, and provide an alternative potential epigenetic strategy for MYCN-driven neuroblastoma treatment.